A study on peripheral neuropathy in HIV infected patients: clinicoepidemiological and electrophysiological profile - Gunasekaran, K.; Sivakumar, S. (International Journal of Research in Medical Sciences, 2018)
Background: Peripheral neuropathy is one among the commonest HIV-associated neurologic complications. The spectrum and the frequency of this complication are changing due to the introduction of new antiretroviral drugs, aging of the HIV-infected people, etc. Hence there is need for a better understanding of these complications and their pathogenesis. This study was done with the aim of finding out the risk factors, clinical characteristics and various types and patterns of peripheral neuropathy in HIV infected patients of our region. Methods: This study was a cross sectional study conducted for about a period of one year. Patients attending the out patient department of anti retroviral therapy (ART) centre were taken for the study. Selected patients were analysed for the signs and symptoms of peripheral neuropathy and they underwent electrophysiological study. Results: Prevalence of peripheral neuropathy in HIV infected patients in our study population was 43.3%. Peripheral neuropathy was seen more in patients with advanced clinical stage and increasing age. Distal symmetric polyneuropathy was the commonest type. Common pathological pattern of neuropathy was mixed (both axonal and demyelination) neuropathy. Conclusions: As peripheral neuropathy is a common HIV-associated neurologic complication, large number of studies are needed to elucidate the mechanisms leading to peripheral neuropathy in HIV infected patients, which in turn will allow for the development of effective therapies that provide adequate symptomatic relief and halt or reverse the damage to the nerves.